The Effect of Ethanol Extract of Calotropis gigantea Root in Increasing the Level of IFN-Î³ and the Expression of Caspase 3 on Mice (Mus musculus L.) with Fibrosarcoma - Muchtaromah, Bayyinatul; Setiawan, Andri; ., Romaidi; Mutiah, Roihatul; Aprinda Kristanti, Risma (International Journal of Engineering and Technology, 2019)
Calotropis gigantea is one of the traditional medicine especially used for cancer treatment. This study aimed to evaluate the effect of ethanol extract of C. gigantea root in increasing the level of IFN-Î³ and the expression of Caspase 3 as a scientific evidence.Â The ethanol extract at dosage of 50, 100 and 150 mg/kg bw were given daily for several weeks on the mice induced by 7,12-dimethylbenz(Î±) anthracene (DMBA). The result revealed that the dosage of 150 mg/kg bw significantly could increase the level of IFN-Î³ and the expression of Caspase 3. In addition, the dosage 150 mg/kg bw also increases the body weight especially after induction of DMBA. This result indicate that the active ingredients of C. gigantea root have a function as immunomodulator agent to increase immune system, initiate apoptosis process and make proliferation disfunction by increasing IFN-Î³ andÂ Caspase 3. This finding showed that C giganteaÂ useful for the treatment ofÂ fibrosarcoma better than methotrexate as anticancer medicine standard.